2018
DOI: 10.1097/fpc.0000000000000339
|View full text |Cite
|
Sign up to set email alerts
|

NAT2 ultra-slow acetylator and risk of anti-tuberculosis drug-induced liver injury

Abstract: This is the first meta-analysis of NAT2 and the risk of ATDILI at the genotypic level. The result demonstrated that NAT2 ultra-slow acetylator genotypes will have the most effect on the increased risk of ATDILI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 42 publications
3
28
0
4
Order By: Relevance
“…In accordance with two previous reports (Leise et al, 2014;Suvichapanich et al, 2018) and the results of the univariate logistic regression in our study, age (threshold value 50 years old), sex, and TB subtypes were considered as covariates in the subsequent multivariate logistic regression analysis. The mutant alleles of rs8085707, rs76986960, and rs949037 were identified as independent risk factors of ATT-DILI (p = 0.004, p = 0.038, and p = 0.040, respectively) ( Table 3).…”
Section: Clinical Characteristics Of Enrolled Patientsmentioning
confidence: 55%
“…In accordance with two previous reports (Leise et al, 2014;Suvichapanich et al, 2018) and the results of the univariate logistic regression in our study, age (threshold value 50 years old), sex, and TB subtypes were considered as covariates in the subsequent multivariate logistic regression analysis. The mutant alleles of rs8085707, rs76986960, and rs949037 were identified as independent risk factors of ATT-DILI (p = 0.004, p = 0.038, and p = 0.040, respectively) ( Table 3).…”
Section: Clinical Characteristics Of Enrolled Patientsmentioning
confidence: 55%
“…The "acetylator trait" describing differences in drugs' acetylation was one of the first identified PGx traits 60 . NAT2 alleles are known to exhibit three phenotypes: rapid, intermediate, and slow acetylators with a variable presentation of these alleles among different populations 61 . Among the few pharmacogenetic studies in the Emirati population, NAT2 was the most studied pharmacogene 62,63 .…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analyses found that rapid acetylators are at increased risk of treatment failure, relapse, and drug resistance [38]. Several studies have proposed pharmacogenomicsguided INH therapy for TB [29,[38][39][40][41][42][43].…”
Section: Isoniazid (Inh)mentioning
confidence: 99%
“…HYD (Figure 2(e)) and SMZ (Figure 3(e)) N-acetylation rates within the slow acetylator phenotype follow the rank order of NAT2*5B/*5B > NAT2*5B/*6A > NAT2*6A/ NAT2*6A in cryopreserved human hepatocytes. A recent review and meta-analysis [39] included 18 studies with 822 cases of anti-tuberculosis drug-induced liver injury and 4630 controls. A more robust association was noted with liver injury in ultra-slow NAT2 acetylators (OR: 3.60; 95% CI: 2.30-5.63) compared to all NAT2 slow acetylators (OR: 2.80; 95% CI: 2.-20-3.57).…”
Section: Genetic Heterogeneity Within the Slow Acetylator Phenotypementioning
confidence: 99%